The politics of transparency and the calibration of knowledge in the digital age. (November 2015) - Hansen, Hans Krause; Flyverbom, Mikkel
This article analyses the complex work of human actors and technologies that goes into producing that which appears to us as 'transparent'. Drawing on studies of governance and surveillance, affordance theory, actor-network theory and sociological work on numbers, we analyse the role played by mediating technologies in the production of transparency and relate it to the question of how knowledge is created, recycled and modified in organizational settings. This perspective is largely absent from existing research on transparency, which construes transparency as unmediated or fails to investigate the organizing properties of specific mediating technologies. We argue that mediating technologies, conceptualized here as disclosure devices, have distinctive organizing properties that are important to scrutinize. They play a central role in attempts to shed light on objects, subjects and practices, and to help build or break up relationships within and across sites and organizations. We focus on three disclosure devices and their respective knowledge creation processes: (a) due diligence, whose emphasis is on qualitative knowledge production; (b) rankings, which is about quantitative knowledge production; (c) big data analysis, which underscores algorithmic knowledge production. We conceptualize the distinct features of these disclosure devices, indicate ways in which they shape organizational processes and discuss some of the ethical and political challenges they pose.